Ecology Of Lesser Sulphur Creasted Cockatoo Cacatua Sulphurea Sulphurea At Rawa Aopa Watumohai National Park, Southeast Sulawesi - Nandika, Dudi; Agustina, Dwi (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018)DO - 10.24843/metamorfosa.2018.v05.i02.p07, 2018)
The Lesser Sulphur-crested cockatoos ( Cacatua sulphurea ) are among the most endangered parrots in Eastern Indonesia. This bird was common species, but since 30 years ago, it was apparent that the decline of the species had been ‘dramatic’ and that it was ‘threatened throughout its range. The best chance to conserve the nominate race lines in Southeast Sulawesi where there is a population of perhaps 50-100 individuals remaining in Rawa Aopa Watumohai National Park [RAWNP]. Direct visualization could be carried out, employing a belt transect and point count method to construct a census. The field research on February until March 2011, founded 55 cockatoos from10 points of all 19 points different survey locations. The research method using scan sampling per 3 menit durations with recorded about 1110 points from 12 days of behavior observations. The daily activities result are: resting 68,9%; moving 21,1%; and eating 10%. On breeding process its begin from grooming or courtship 9 menits and mating 83 seconds. Cockatoos eating proportion: fruits 64,3%; flowers 14,3%; young leafs 14,3% and seeds 7,1%. The research founded eight nestholes trees, from Kolaka Parinarium carymbosum and Kuiya Alatonia scholaris . The cockatoo daily activites and habitat conditions are based data for  supporting conservation habitat management in the future.